Tie points for manual alignment of the benthic foraminiferal δ^1?O record at ODP Site 1090 to LR04 - Jenny Middleton; Julia Gottschalk; Gisela Winckler; Jean Hanley; Carol Knudsen; Jesse R Farmer; Lorraine E Lisiecki; Frank Lamy (PANGAEA, 2024)
This dataset presents user-defined tiepoints of the manual alignment of the benthic foraminiferal δ^1?O record at ODP Site 1090 to the benthic foraminiferal LR04 δ^1?O stack of Lisiecki and Raymo (2005) obtained by Middleton et al. (2024). The benthic foraminiferal δ^1?O record is based on Cibicidoides wuellerstorfi and was previously published in Hodell et al. (2000) and Venz and Hodell (2002).
In: Middleton, J et al. (2024): Benthic foraminiferal δ^1?O alignments for IODP Site U1541, ODP Site 1090 and ODP Site 980-981 based on different tuning targets for the past ~3.5 Myr [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.965845